High adherence to angiotensin-converting enzyme inhibitor in children and adolescents with Alport syndrome: objective verification using liquid chromatography-mass spectrometry - Boeckhaus, Jan; Tönshoff, Burkhard; Weber, Lutz T.; Haffner, Dieter; Pape, Lars; Latta, Kay; Fehrenbach, Henry; Lange-Sperandio, Baerbel; Kettwig, Matthias; König, Sabine; John-Kroegel, Ulrike; Gellermann, Jutta; et al. (Pediatric Nephrology, 2025)
Background: Kidney failure (KF) in children and adolescents leads to reduced lifespan and compromised health. Alport syndrome (AS) is a leading hereditary cause of KF in children. Angiotensin-converting enzyme inhibitors (ACEi) have demonstrated efficacy in delaying KF in young people living with AS, but non-adherence can compromise their therapeutic benefits. To investigate the adherence to ACEi in children and adolescents with AS, a liquid chromatography-mass spectrometry (LCMS)-based method was developed for objective verification of recent medication intake at two different time points in this cohort study. Methods: Urine samples from 58 children enrolled in the EARLY PRO-TECT Alport trial were analyzed. An LCMS-based method was established and validated to simultaneously screen and quantify both ramipril and ramiprilat in urine samples. Participants were not informed in advance of the medication intake measurements. Results: A total of 106 urine samples from 58 patients with early stages of chronic kidney disease (mean estimated glomerular filtration rate, 130 ± 32 mL/min/1.73 m2) were analyzed at two different time points. All 13 negative control samples (100%; 95% confidence intervals [CI] 75.7% to 100%) were identified correctly. Adherence to ACEi at the time of sampling was consistently high, with 96% (47/49; 95% CI 86% to 99.5%) and 95% (42/44; 95% CI 84.5% to 99.4%) of children showing confirmed drug intake at initial and second adherence measurements. Conclusion: This study demonstrated that children with chronic kidney disease, when treated with ACEi within a clinical trial, show high adherence to the prescribed medication.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Adherence; Alport syndrome; Clinical trial; Hereditary kidney disease; Ramipril